IDENTIFICATION OF RADIAL VASCULAR WALL ABNORMALITIES BY VERY-HIGH FREQUENCY ULTRASOUND IN FIBROMUSCULAR DYSPLASIA AND SPONTANEOUS CORONARY ARTERY DISSECTION: THE FUCHSIA STUDY. (June 2018) - Bruno, R.M.; Di lascio, N.; Al Hussaini, A.; Guarino, D.; Vitali, S.; Rossi, P.; Caramella, D.; Taddei, S.; Faita, F.; Ghiadoni, L.; Adlam, D.; Persu, A.; et al.
Abstract : Objective: Fibromuscular dysplasia (FMD) is an idiopathic disease of small-and medium-sized arteries. Subclinical alterations have been found also in non-affected segments, suggesting that FMD is a systemic disease. Spontaneous coronary dissection (SCAD) may represent a manifestation of FMD too. This case-control study is aimed at identifying vascular wall abnormalities in the radial arteries in patients with FMD and SCAD by means of a novel ultrasound technique. Figure. No caption available. Design and method: Two 5′-clips from the left radial artery were obtained by Vevo MD (70 MHz probe, FUJIFILM, VisualSonics). Radial wall showed two echogenic interfaces: the 1st (lumen-media) and the 2nd (media-adventitia). Intima-media (IMT), adventitia (AT), and global thickness (IMAT) and wall cross-sectional area (WCSA) Measured. Vascular wall disarray was assessed calculating the root mean square error (RMSE) between 20 gray-level profiles crossing the two interfaces and the profile obtained averaging them, normalized for the maximum value of the corresponding mean profile (RMSE/mean). Results: 12 SCAD patients, 21 FMD patients and 12 healthy controls (C), matched for age (51 ± 12, 47 ± 7, 43 ± 12, p = 0.12) and sex (2 M, 1 M, 2 M), were enrolled. IMT (0.182 ± 0.056, 0.170 ± 0.033, 0.133 ± 0.020 mm, p = 0.01), AT (0.108 ± 0.027, 0.116 ± 0.029, 0.076 ± 0.014 mm, p = 0.001) and IMAT (0.290 ± 0.076, 0.286 ± 0.045, 0.209 ± 0.029 mm, p = 0.001), were significantly higher in SCAD and FMD compared to C. WCSA, but not M/L, was increased too in SCAD and FMD. RMSE/mean was significantly increased in SCAD and FMD compared to controls either in the 1st (1.48 ± 0.84, 1.28 ± 0.52, 0.74 ± 0.26, p = 0.01) or in the 2nd interface (2.44 ± 1.38, 1.56 ± 0.58, 1.19 ± 0.93 p = 0.01). Conclusions: The radial artery walls of FMD and SCAD patients present similar subclinical abnormalities, namely increased thickness and and inhomogeneity, in comparison to controls.